Effect of Birth Weight and Socioeconomic Status on Children's Growth in Mashhad, Iran - Ashraf Mohammadzadeh; Ahmadshah Farhat; Rana Amiri; Habibollah Esmaeeli (Hindawi Limited, 2010)
Background. Socioeconomic status and birth weight are prominent factors for future growing of children. Also Studies show that this criterion is associated with reduced cognitive outcomes, school achievement, and adult work capacity. So in this paper we determined the effects of some socio-economic statuses and birth weight on physical growth of children in Mashhad, Iran. Method and materials. This is a cross sectional study that determined effect of socio-economic status and birth weight on weight, heighting and BMI of school age children. Healthy six years old children who were screened before enter, to school were eligible for participating in our study between 6 June 2006 and 31 July. Weight and standing height were documented at birth and measured at 6 years old. Then, their BMI were calculated in childhood period. Data were analyzed by using SPSS software. Result. Results show that some socio-economic variables and birth weight is associated with and, perhaps, influence the variation of growth in the children. The variables which show the most consistent and significant association were birth weight, sex, economic status and education of parents. Conclusion. In this paper, we found that birth weight, economic status and education parents of neonates have directly significant effect on growth childhood period. We recommended that paying attention to these criteria for improving growth of children in our society should be considered by authorities.